Validation of the Italian version of the peritraumatic distress inventory: validity, reliability and factor analysis in a sample of healthcare workers. Issue 1 (1st January 2021) - Carmassi, Claudia; Bui, Eric; Bertelloni, Carlo A.; Dell'Oste, Valerio; Pedrinelli, Virginia; Corsi, Martina; Baldanzi, Sigrid; Cristaudo, Alfonso; Dell'Osso, Liliana; Buselli, Rodolfo
ABSTRACT: Background : Peritraumatic distress as assessed by the Peritraumatic Distress Inventory (PDI), has been consistently shown to predict the development of Posttraumatic Stress Disorder (PTSD) after the exposure to a potentially traumatizing event. Objective : The present study aims to validate the Italian version of the PDI in a sample of Healthcare Workers (HCWs) exposed to COVID-19 related potentially traumatizing events. Method : N = 265 HCWs who repeatedly experienced the deaths of patients during COVID-19 emergency in Italy, were enrolled from the Azienda Ospedaliero-Universitaria Pisana (Pisa, Italy). They completed the PDI, Impact Event Scale – revised (IES-R) and the reactions to losses or upsetting events Trauma and Loss Spectrum – Self Report (TALS-SR) domain. Results : Internal consistency was good with a Cronbach's alpha coefficient was .874. The PDI correlated strongly with measures that was conceptually close (TALS-SR reactions to losses or upsetting events domain; r = .723, p < .001). Participants who scored above the cut-off for PTSD reported significantly higher PDI scores than those who did not (6.47 ± 5.25 vs. 19.11 ± 8.291, p < 0.001). The one-month test–retest reliability ( n  = 21) was excellent (ICC = .997). Finally, factor analyses revealed that the PDI exhibited a single-factor structure. Conclusions : the Italian version of the PDI showed good psychometric proprieties and may be used to detect those at risk for developing PTSD. HIGHLIGHTS: Study aim: to validate the Italian version of the peritraumatic distress inventory (PDI). 265 Healthcare Workers completed the PDI the IES-R and the TALS-SR. The reliability, internal consistency validity and the temporal stability were good. The tool presented a one-factor structure.